Myocardial edema without fibrosis by magnetic resonance T2 mapping in acute Chagas' myocarditis - Sousa, Andrea Silvestre de (2017)
Fundação Oswaldo Cruz. Instituto Nacional de Infectologia Evandro Chagas. Rio de Janeiro, RJ, Brasil /Universidade Federal do Rio de Janeiro. Hospital Universitário Clementino Fraga Filho. Rio de Janeiro, RJ, Brasil.